Development of Forms of the Hotel Business Organization in Modern Conditions - KONOVALOVA, Elena Evgenievna; SHELYGOV, Aleksandr Vladimirovich; ARTAMONOVA, Larisa Sergeevna; DOLINA, Olga Nikolaevna; BOIKOV, Aleksandr Igorevich (Journal of Environmental Management and Tourism; Vol 11 No 4 (2020): JEMT Volume XI Issue 4(44) Summer 2020DO - 10.14505//jemt.v11.4(44).09, 2020)
The article is devoted to the development of forms of the hotel business in modern conditions. The authors have established that the modern typology of accommodation facilities is determined by the development of recreational infrastructure and its provision with statutory and operation-al acts, as well as the identification of functional and technological structures. It has been proven that Russian hotel services classification system considers the main criteria for the assessment of service quality and cur-rent state of the material and technical base of all types of hotels and their specialization. The authors have determined that modern competitive advantages of the hotel business development can include the global information system, deeper specialization of hotel complexes, development of small hotel chains, introduction of computer technologies, establishment of international hotel chains, and adaptation and balanced approach to consumer needs. It has been identified that the main option of running a hotel can be the independent management of a hotel, the independent management with the participation of a hotel association, the independent management under a franchise agreement, the leasing of the operator’s property, and the signing of a management agreement with an independent hotel operator.